Nano-sized phase inclusions in As₂S₃ glass, films and fibers based on this glass - Mateleshko, N.; Mitsa, V.; Stronski, A.; Veres, M.; Koos, M.; Andriesh, A.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2004)
In this report, the comparative analysis using Raman spectroscopy of the short-range order in amorphous As₂S₃ films deposited with different evaporation rates, volume glass and fiber based on this glass is presented. With increasing the film deposition rate, their structure becomes more non-uniform as compared to that of glass. Raman spectra excited by laser radiation with energy bigger than the width of the optical gap indicate photomodification of the structure of As₂S₃ glass and fiber based on it.